2019
DOI: 10.1186/s12864-019-6208-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and tissue-specific transcriptome analyses and expression profiling of olfactory-related genes in Ceracris nigricornis Walker (Orthoptera: Acrididae)

Abstract: BackgroundThe sophisticated insect olfactory system plays an important role in recognizing external odors and enabling insects to adapt to environment. Foraging, host seeking, mating, ovipositing and other forms of chemical communication are based on olfaction, which requires the participation of multiple olfactory genes. The exclusive evolutionary trend of the olfactory system in Orthoptera insects is an excellent model for studying olfactory evolution, but limited olfaction research is available for these sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 91 publications
2
9
0
Order By: Relevance
“…In general the number of olfactory gene family candidate transcripts were consistent with that of other species ( Liu et al, 2012 ; Pitts et al, 2011 ; Riveron, Boto & Alcorta, 2013 ), except for CSP and IR. We also found that the expression difference of olfactory genes between the sexes is consistent to that of other insects ( Leitch et al, 2015 ; Li et al, 2018 ; Yuan et al, 2019 ; Zhao et al, 2018 ). In addition, some olfactory genes are highly expressed in other organs (head, leg or wing) rather than antennae.…”
Section: Discussionsupporting
confidence: 85%
“…In general the number of olfactory gene family candidate transcripts were consistent with that of other species ( Liu et al, 2012 ; Pitts et al, 2011 ; Riveron, Boto & Alcorta, 2013 ), except for CSP and IR. We also found that the expression difference of olfactory genes between the sexes is consistent to that of other insects ( Leitch et al, 2015 ; Li et al, 2018 ; Yuan et al, 2019 ; Zhao et al, 2018 ). In addition, some olfactory genes are highly expressed in other organs (head, leg or wing) rather than antennae.…”
Section: Discussionsupporting
confidence: 85%
“…In general the number of olfactory gene family candidate transcripts were consistent with that of other species (Liu et al 2012;Pitts et al 2011;Riveron et al 2013), except for CSP and IR. We also found that the expression difference of olfactory genes between the sexes is consistent to that of other insects (Leitch et al 2015;Yuan et al 2019;Zhao et al 2018). In addition, some olfactory genes are highly expressed in other PeerJ reviewing PDF | (2019:12:44386:2:1:NEW 24 Jun 2020)…”
Section: Discussionsupporting
confidence: 82%
“…The NR annotation revealed that the species with the largest distribution of unigenes in G. licenti and M. japonicus was Z. nevadensis rather than more closely related L. migratoria, which may be caused by the incomplete genome assembly of L. migratoria 17 . But compared with published RNA-seq of the Acrididae species, unigenes obtained by PacBio sequencing has a higher proportion of annotation on the genomes of L. migratoria 18,19,62 . The KEGG analysis showed that 209 and 211 KEGG pathways were successfully annotated in G. licenti and M. japonicus, respectively.…”
Section: Discussionmentioning
confidence: 94%